Resisting the "Attachment Disruption" of Colonisation Through Decolonising Therapeutic Praxis: Finding Our Way Back to the Homelands Within - Riel Dupuis-Rossi (Psychotherapy and Counselling Journal of Australia)
This article provides a theoretical framework and practical applications for an Indigenous-centred decolonising therapeutic practice. I define and critique the concept of the "attachment disruption" of colonisation and its impacts on Indigenous Peoples and, specifically, Indigenous clients. I discern and differentiate colonial forms of power, which are based in domination and violence, from Indigenous forms of power rooted in cultural traditions and connections to ancestral territories. Case examples illustrate ways of working therapeutically with the "attachment disruption" of colonisation as it concerns "residential school trauma," "lateral violence," and "addictions". The importance of externalising the impacts of colonial violence and centring Indigenous cultural and relational imprints is the foundation of this decolonising therapeutic praxis.